Clinical Assessment of Ventricular Wall Stress in Understanding Compensatory Hypertrophic Response and Maladaptive Ventricular Remodeling - Takeshi Tsuda (Journal of Cardiovascular Development and Disease, 2021)
Ventricular wall stress (WS) is an important hemodynamic parameter to represent myocardial oxygen demand and ventricular workload. The normalization of WS is regarded as a physiological feedback signal that regulates the rate and extent of ventricular hypertrophy to maintain myocardial homeostasis. Although hypertrophy is an adaptive response to increased biomechanical stress, persistent hypertrophic stimulation forces the stressed myocardium into a progressive maladaptive process called ventricular remodeling, consisting of ventricular dilatation and dysfunction in conjunction with the development of myocyte hypertrophy, apoptosis, and fibrosis. The critical determinant of this pathological transition is not fully understood, but an energetic mismatch due to uncontrolled WS is thought to be a central mechanism. Despite extensive basic investigations conducted to understand the complex signaling pathways involved in this maladaptive process, clinical diagnostic studies that translate these molecular and cellular changes are relatively limited. Echocardiographic assessment with or without direct measurement of left ventricular pressure used to be a mainstay in estimating ventricular WS in clinical medicine, but in recent years more and more noninvasive applications with magnetic resonance imaging have been studied. In this review article, basic clinical applications of WS assessment are discussed to help understand the progression of ventricular remodeling.